Structure, degradation, drug release and mechanical properties relationships of iron-based drug eluting scaffolds: The effects of PLGA - Yusop, Abdul Hakim; Sarian, Murni Nazira; Januddi, Fatihhi Szali; Ahmed, Qamar Uddin; Kadir, Mohammed Rafiq; Hartanto, Djoko; Hermawan, Hendra; Nur, Hadi (Elsevier, 2018)
The effects of poly(lactic‑co‑glycolic acid) (PLGA) on structure, degradation, drug release and mechanical properties relationships of iron-based drug eluting scaffolds have been studied comprehensively. The porous structure of the iron has been incorporated with the curcumin-loaded PLGA (CP) particles through dipping method to produce CP-coated porous Fe (CP-Fe). The CP-Fe degradation has been escalated with the increase of PLGA composition due to the hydrolysis of PLGA. The degradation of iron substrate triggered the kinetics of curcumin release as there was a direct correlation between the curcumin release rate and the degradation rate of the CP-Fe scaffold. The stiffness of the CP particles and the interfacial interactions developed between the CP coating and iron surface have enhanced scaffolds' mechanical strengths. The curcumin released from the scaffold significantly arrested osteosarcoma cells growth. It is demonstrated that the PLGA played an important role to control the scaffold degradation and curcumin release as well as enhancing the mechanical properties of the drug device as an integrated system for favorable scaffold-based drug design.